The effect of nanofiber surface modification on osteogenic stem cell differentiation - Onak, Günnur. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2019., 2019)
Optimization of nanoﬁber (NF) surface properties is critical to achieve an adequate cell response. Here, the impact of conjugation of biomimetic aspartic (ASP) and glutamic acid (GLU) templated peptides with PLGA electrospun NF on osteogenic differentiation of bone marrow stromal cells (BMSCs) was evaluated. Cold atmospheric plasma (CAP) was used to functionalize the NF surface and thus to mediate the conjugation. The inﬂuence of the CAP treatment following with peptide conjugation to the NF surface was assessed using scanning electron microscopy (SEM), contact angle measurements, Fourier-transform infrared spectroscopy (FTIR) and X-ray photoelectron spectroscopy (XPS), Both the hydrophilicity of NFs and the number of the -COOH groupsonthesurfaceincreasedwithrespecttothedurationofCAPtreatment. Results demonstrated that CAP treatment signiﬁcantly enhanced peptide conjugation on surface of NF. Osteogenic diﬀerentiation results indicated that conjugating of biomimetic ASP templated peptides sharply increased alkaline phosphatase (ALP) activity, calcium content, and expression of key osteogenic markers of collagen type I, osteocalcin, and osteopontin compare to GLU conjugated and neat NF. It was further depicted that ASP sequences are the major fragments that inﬂuence mineralization and osteogenic diﬀerentiation in non-collagenous proteins of bone extracellular matrix.|Keywords : Bone tissue engineering, Peptide, Scaﬀold, Surface functionalization.
Keywords: Nanofibers.; Bone regeneration.; Peptide drugs.; Tissue engineering.